The Students’ Perception toward Reward and Punishment to Increase Their Motivation in Learning English - Cici Afriyeni; M. Zaim (Universitas Negeri Padang, 2023)
The purpose of this study is to find out the students’ perception toward reward and punishment in learning English, kinds of reward and punishment given by the teacher in learning English, and how reward and punishment increase students’ motivation in learning English. This research uses descriptive method. A total of 68 of the eleventh grade students in SMAN 12 Padang are chosen using cluster random sampling method. Observation, questionnaire, and interview are used to collect the data. The results of this study show; (1) Teacher gives several kinds of reward in learning English, namely material or symbolic reward, teacher-based reward, preferred activity reward, and good school report reward. (2) Teacher gives several kinds of punishment in learning English, namely symbolic punishment, teacher-based punishment, curtailment activity punishment, home-linked punishment, memorizing vocabularies, and changing students’ seating arrangement. (3) The students have very positive perception toward reward in learning English. (4) The students have positive perception toward punishment in learning English. (5) Reward can encourage students to study harder and punishment give deterrent effect on students. In conclusion, the students have very positive perception toward reward and punishment in learning English. Moreover, reward and punishment affected students’ motivation in learning English.